Climate change in rural Ghana: perceptions and adaptive responses. Issue 12 (2nd December 2021) - Addaney, Michael; Asibey, Michael Osei; Cobbinah, Patrick Brandful; Akudugu, Jonas Ayaribilla
ABSTRACT: The purpose of this study is threefold: (i) to analyse local perceptions on climate change and events; (ii) to examine the impact of climate change on local livelihoods and food security and (iii) to explore climate change adaptive responses and challenges thereof. Using the Dormaa West District in Ghana as a case study, data were obtained from 190 household participants across randomly selected five communities; five focus group discussions and interviews with four planning and climate agencies. Both quantitative and qualitative techniques were employed to analyse the collected data. The results showed evidence of climate change with widespread impacts on local livelihood, particularly food production. There is evidence of unpredictable precipitation and warming temperatures over the past two decades with a high degree of variability. Key adaptive response measures included reliance on remittances, engaging in secondary livelihoods (e.g. driving and petty trading), and adjusting growing and harvesting seasons. Unfortunately, these measures were ad hoc, reactionary and unsustainable. The incorporation of farmer-based adaptation strategies into development and management plans, stakeholder participation, collaborations and partnerships are imperative in finding effective and sustainable adaptive response measures.